The legacy of Luiz Beltrão from the perspective of José Marques de Melo (Revista Internacional de Folkcomunicação, 2018)
This paper has the focus about the relationship between the autor of this study with Beltrão and his work. The paper detach the role of Luiz Beltrão works and the strategic influence of José Marques de Melo to spread the Folkcomunication theory. Folkcomunicação; Luiz Beltrão; José Marques de Melo; INTERCOM.